Pengaruh Gross Profit Margin, Quick Ratio, dan Debt To Asset Ratio Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi SUB Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2 - Aelok Tabah Mungawanah; Dewi Shanti; Hesti Respatiningsih (STIE Rajawali Purworejo, 2024)
This research examines empirically the effect of Gross Profit Margin (GPM), Quick Ratio (QR), and Debt to Asset Ratio (DAR) to Company Values in manufacturing companiesin the consumer goods industry sector, food and beverage sub sector for the period 2020 – 2022. The ones in this research are all finance reports of food and baverage sub sector manufacturing companies that passed the sampling criteria for 3 years from 2020 – 2022. The sampling method was carried out using the purposive sampling method. The type of data analysis used in this research is quantitative data, with descriptive statistical analysis, classical assumption test, multiple linier regression, coefficient of determination and multiple correlation, partial test (T test) and simultaneous test (F test) using the SPSS version 16 application. This research shows that Gross Profit Margin (GPM), Quick Ratio (QR) and Debt to Asset Ratio (DAR) have a positive effect on Company alue in Manufacturing Companies in the Consumer Goods Industry sector, food and baverage sub-sector for period 2020 – 2022. Based on simultaneous testing, it states that Gross Profit Margin (GPM), Quick Ratio (QR) and Debt to Asset Ratio (DAR) simultaneously have a significant effect on Company Value in Manufacturing Companies in the Consumer Goods Industrial sector, food and beverage sub-sector for the period 2020 – 2022.